THE PRESENTATION OF GERMAN HOLIDAYS AND TRADITIONS IN TEXTBOOKS - Dilnoza Yusupova Uktamali qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article is devoted to the presentation of German holidays and traditions in textbooks and how they affect the worldview of students , in wich the topics of German language lessons are studied. The celebration and significance of such celebrations and traditions increases the interest of students in the study of the traditions of other nations. The article describes the various holidays and traditions of the German people.